IPO Underpricing Factors: Technology and Non-Technology Sectors in Terms of Information Asymmetry and Retention of Control Theories - A. A. Galich; A. G. Mirzoyan (Финансы: теория и практика, 2025)
This study investigates the relationship between the underpricing of company stocks in initial public offerings (IPOs) and the key factors associated with two dominant theories: information asymmetry and retention of control. The main objective of the study is to determine which factors considered by the two theories affect stock underpricing in the technology and non-technology sectors. Multiple regression models are used to identify the significant factors of underpricing for each sector, and the adjusted coefficient of determination is used to compare the explanatory power of the models of each theory. The sample includes 321 IPOs launched between 2000 and 2020 on the leading US exchanges NYSE and NASDAQ. The results show that in the technology sector, the significant predictors of underpricing are research and development (R&D) costs, the age of the company at the time of going public, and the Roll-up strategy. In the nontechnology sector, the key underpricing factors are the proportion of publicly traded shares and the age of the company. It is concluded that the theory of information asymmetry demonstrates the greatest explanatory power in the context of the technological sector, which indicates the significant influence of information barriers on the formation of market prices. At the same time, in the non-technology sector, the predictive power of regression models was significantly lower, which indicates the need for further search and analysis of additional factors affecting the undervaluation of shares in this sector. Thus, this study contributes to a deeper understanding of IPO undervaluation mechanisms, emphasizing the importance of taking into account the specifics of different industry segments when analyzing and forecasting market processes.